The Effectiveness of Educational Media on Knowledge, Dietary Patterns and Compliance with Iron Supplement Consumption in Anemic Adolescent Girls - Ade Damayanti Raihani; Riana Pangestu Utami; Rinten Anjang Sari (Journal of Health and Nutrition Research, 2024)
The aim of this research is to analyze the effectiveness of educational media on knowledge, eating patterns, and compliance with the Iron supplement consumption in anemic teenagers at Senior High School, SMKN 15 Samarinda. The type of research used was quasi-experimental, and the research design used a pre-test and post-test with a control group research design. The population was all 621 female students, and 72 people were screened; then, the sample was obtained from about 30 respondents by hemoglobins quick check. The sample was determined as 15 people for the flipchart media group with leaflets and 15 people for the leaflet media group. Data were analyzed using univariate and bivariate analysis. The results of the research were that anemic teenagers consisted of teenagers aged 12-16 years with a percentage of 73.3%. Educational media influenced knowledge (p 0.008) and compliance with iron supplement consumption (p 0.028) of anemic adolescents. There was no effect of educational media on the diet of anemic adolescents as sources of animal protein (p 0.217), vitamin C (p 0.217), and Fe inhibitors (p 0.217). This study concludes that education using flipcharts and leaflets has an effect on increasing knowledge and consumption of iron supplement tablets